Epac as a tractable therapeutic target - Hasan Slika (17821427) (2023)
In 1957, cyclic adenosine monophosphate (cAMP) was identified as the first secondary messenger, and the first signaling cascade discovered was the cAMP-protein kinase A (PKA) pathway. Since then, cAMP has received increasing attention given its multitude of actions. Not long ago, a new cAMP effector named exchange protein directly activated by cAMP (Epac) emerged as a critical mediator of cAMP's actions. Epac mediates a plethora of pathophysiologic processes and contributes to the pathogenesis of several diseases such as cancer, cardiovascular disease, diabetes, lung fibrosis, neurological disorders, and others. These findings strongly underscore the potential of Epac as a tractable therapeutic target. In this context, Epac modulators seem to possess unique characteristics and advantages and hold the promise of providing more efficacious treatments for a wide array of diseases. This paper provides an in-depth dissection and analysis of Epac structure, distribution, subcellular compartmentalization, and signaling mechanisms. We elaborate on how these characteristics can be utilized to design specific, efficient, and safe Epac agonists and antagonists that can be incorporated into future pharmacotherapeutics. In addition, we provide a detailed portfolio for specific Epac modulators highlighting their discovery, advantages, potential concerns, and utilization in the context of clinical disease entities. Other Information Published in: European Journal of Pharmacology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ejphar.2023.175645